A study of human vocal effort in response to the architectural auditory environment. (3rd July 2020) - Alambeigi, Pantea; Burry, Jane; Zhao, Sipei; Cheng, Eva
Abstract : This paper examines human auditory interaction with an architectural design hypothesized to decrease users' vocal effort and thus enhance their speech privacy. This detailed design increased sound scattering in semi-enclosed meeting rooms within open plan offices. To achieve desirable speech intelligibility, a live sound environment is strongly recommended for meeting rooms. The research explores the hypothesis that by adding early reflections to the direct sound energy with an integrated design, the speaker as a self-listener might benefit from perceiving their own voice with more clarity. This can cause adaptive changes to subconscious vocal effort and increase the corresponding speech privacy of the space. An architecture-driven talker-quality experiment in a natural situation has been conducted in two rounds and in two different acoustic environments with 20 participants. The results implied the importance of human visual and spatial perception of privacy over auditory interaction with the environment on decreasing vocal effort. Such factors could thus be considered within the architectural design process.